The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

From pixels to patterns: Coupling Optical Coherence Tomography and machine learning for monitoring coastal wetland root systems - Mohamed O. Hassan; Aramy Truong; Maruti Mudunuru; Leslie G. Butler; Andre Rovai; Curtis Larimer; Joseph Daddona; Amir H. Ahkami; Jay Bardhan; Tamas Varga; Kelly Stratton; Satish Karra; et al. (Science of The Total Environment, 2025)

Multi‐decadal climate and fishing predictors of abundance for U.S. South Atlantic coastal fishes and invertebrates - Mark A. Stratton; Geneviève M. Nesslage; Robert J. Latour (Fisheries Oceanography, 2019)
Abundance of marine stocks fluctuates in response to both internal processes (e.g., density dependence) and exogenous drivers, including the physical environment, fishing, and trophodynamic interactions. In the United States, research investigating ecosystem drivers has been focused in data‐rich systems, primarily in the North Atlantic and North Pacific. To develop a more holistic understanding of important ecosystem drivers in the Southeast U.S. continental shelf Large Marine Ecosystem, we applied generalized linear and dynamic linear modeling to investigate the effects of climate and fishing covariates on the relative abundance trends of 71 demersal fish and invertebrate species sampled by a coastal trawl survey during 1990–2013. For the assemblage as a whole, fishing effects predominated over climate effects. In particular, changes in trawling effort within the penaeid shrimp fishery governed abundance trends of bony fishes, invertebrates, and elasmobranchs, a likely result of temporal changes in bycatch mortality. Changes in trawling intensity induced changes in overall community composition and appear to have altered trophic interactions among particular species. Among climate indices investigated, the Pacific Decadal Oscillation and the Western Bermuda High Index were most prevalent in well‐supported dynamic linear models. Observed annual abundance trends were synchronous among some taxonomically related species, highlighting similar responses to exogenous influences based on life history. This study strengthens the foundation for generating hypotheses and advancing ecosystem‐based fisheries research within the region.

Improved climatological precipitation characteristics over West Africa at convection-permitting scales - Ségolène Berthou; David P. Rowell; Elizabeth J. Kendon; Malcolm J. Roberts; Rachel A. Stratton; Julia A. Crook; Catherine Wilcox (Climate Dynamics, 2019)

Dispersal limitations on fish community recovery following long-term water quality remediation - Ryan A. McManamay; Robert T. Jett; Michael G. Ryon; Scott M. Gregory; Sally H. Stratton; Mark J. Peterson (Hydrobiologia, 2016)

Establishing a reference group for distal 18q-: clinical description and molecular basis - Jannine D. Cody; Minire Hasi; Bridgette Soileau; Patricia Heard; Erika Carter; Courtney Sebold; Louise O’Donnell; Brian Perry; Robert F. Stratton; Daniel E. Hale (Human Genetics, 2014)

A Method for Ensemble Wildland Fire Simulation - Mark A. Finney; Isaac C. Grenfell; Charles W. McHugh; Robert C. Seli; Diane Trethewey; Richard D. Stratton; Stuart Brittain (Environmental Modeling & Assessment, 2011)

Levels of gene flow among populations of a wolf spider in a recently fragmented habitat: current versus historical rates - David H. Reed; View-Hune Teoh; Gail E. Stratton; Robert A. Hataway (Conservation Genetics, 2011)

Younger age-at-diagnosis for familial malignant testicular germ cell tumor - Phuong L. Mai; Bingshu E. Chen; Kathy Tucker; Michael Friedlander; Kelly-Anne Phillips; David Hogg; Michael A. S. Jewett; Istvan Bodrogi; Lajos Geczi; Edith Olah; Ketil Heimdal; Sophie D. Fosså; et al. (Familial Cancer, 2009)

A long term assessment of phosphorus treatment by a constructed wetland receiving dairy wastewater - Jeffrey D. Wood; Robert Gordon; Ali Madani; Glenn W. Stratton (Wetlands, 2008)

Refined mapping of X-linked reticulate pigmentary disorder and sequencing of candidate genes - Lane J. Jaeckle Santos; Chao Xing; Robert B. Barnes; Lesley C. Ades; Andre Megarbane; Christopher Vidal; Angela Xuereb; Patrick S. Tarpey; Raffaella Smith; Mahmoud Khazab; Cheryl Shoubridge; Michael Partington; et al. (Human Genetics, 2008)

Mutations in PATCHED-1, the receptor for SONIC HEDGEHOG, are associated with holoprosencephaly - Jeffrey Ming; Michelle Kaupas; Erich Roessler; Han Brunner; Mahin Golabi; Mustafa Tekin; Robert Stratton; Eva Sujansky; Sherri Bale; Maximilian Muenke (Human Genetics, 2002)

Mutations in PATCHED-1, the receptor for SONIC HEDGEHOG, are associated with holoprosencephaly - Jeffrey E. Ming; Michelle E. Kaupas; Erich Roessler; Han G. Brunner; Mahin Golabi; Mustafa Tekin; Robert F. Stratton; Eva Sujansky; Sherri J. Bale; Maximilian Muenke (Human Genetics, 2002)

Technique for identifying and minimizing solvent-pesticide interactions in bioassays - Glenn W. Stratton; Robert E. Burrell; Charles T. Corke (Archives of Environmental Contamination and Toxicology, 1982)